Investing in impact : mid-year results report 2006 (The Global Fund GenevaCH, 2006)
Sets out the achievements and challenges of the Global Fund's performance-based funding model. Examines the steps required to go from approved grant funding to impact on three diseases viz. HIV/AIDS, tuberculosis and malaria. Examines also, the Fund's contributions to wider international targets such as the Millennium Development goals.
Keywords: GRANTS